One and Multiple Bonds Interatomic Spin-Spin Coupling in η6-Cymene Ru(II) of 3,5-Dimethyl-, 3,5-Dicarboxylic-, and 5-Phenyl-pyrazole Derivatives - Adeniyi, Adebayo A.; Ajibade, Peter A. (Journal of Spectroscopy, 2015)
The changes in the interatomic distances and the corresponding spin-spin coupling as a result of the hydrolysis of the ruthenium complexes and the effects of different derivatives of the pyrazole ligands and the substituents methyl, carboxylic, and phenyl on the pyrazole rings were studied. A good agreement was obtained between the experimental and the theoretical proton NMR. Significant changes are observed in the isotropic and anisotropic shielding tensor of the atoms and related spin-spin coupling of their bonds due to hydrolysis of the complexes. This observation gives more insight into the known mechanism of activation of the ruthenium complexes by hydrolysis. There are no direct effects of interatomic distances on many of the computed spin-spin couplings with the exception of 1J(Ru-N) which shows significant changes especially within the pair of 1J(Ru-N) in the complexes with two nitrogen atoms of the bis-pyrazole moiety. The magnitude of interatomic spin-spin coupling of the Ru-X follows the order of Ru-Cl > Ru-N > Ru-C > Ru-O. The Ramsey term Fermi contact (FC) has the most significant contribution in most of the computed spin-spin interactions except in 1J(Ru-Cl) and 1J(N-N⁎) which are predominantly defined by the contribution from the paramagnetic spin orbit (PSO).